Seamless Gene Correction in the Human Cystic Fibrosis Transmembrane Conductance Regulator Locus by Vector Replacement and Vector Insertion Events - Suzuki, Shingo; Chosa, Keisuke; Barillà, Cristina; Yao, Michael; Zuffardi, Orsetta; Kai, Hirofumi; Shuto, Tsuyoshi; Suico, Mary Ann; Kan, Yuet W.; Sargent, R. Geoffrey; Gruenert, Dieter C. (Frontiers in Genome Editing, 2022)
Background: Gene correction via homology directed repair (HDR) in patient-derived induced pluripotent stem (iPS) cells for regenerative medicine are becoming a more realistic approach to develop personalized and mutation-specific therapeutic strategies due to current developments in gene editing and iPSC technology. Cystic fibrosis (CF) is the most common inherited disease in the Caucasian population, caused by mutations in the CF transmembrane conductance regulator (CFTR) gene. Since CF causes significant multi-organ damage and with over 2,000 reported CFTR mutations, CF patients could be one prominent population benefiting from gene and cell therapies. When considering gene-editing techniques for clinical applications, seamless gene corrections of the responsible mutations, restoring native “wildtype” DNA sequence without remnants of drug selectable markers or unwanted DNA sequence changes, would be the most desirable approach. Result: The studies reported here describe the seamless correction of the W1282X CFTR mutation using CRISPR/Cas9 nickases (Cas9n) in iPS cells derived from a CF patient homozygous for the W1282X Class I CFTR mutation. In addition to the expected HDR vector replacement product, we discovered another class of HDR products resulting from vector insertion events that created partial duplications of the CFTR exon 23 region. These vector insertion events were removed via intrachromosomal homologous recombination (IHR) enhanced by double nicking with CRISPR/Cas9n which resulted in the seamless correction of CFTR exon 23 in CF-iPS cells. Conclusion: We show here that removal of the drug resistance cassette and generation of seamless gene corrected cell lines by two independent processes: by treatment with the PiggyBac (PB) transposase in vector replacements or by IHR between the tandemly duplicated CFTR gene sequences.